A Review of Safeguarding Cases in Sport. (18th February 2014) - Rhind, Daniel; McDermott, Jamie; Lambert, Emma; Koleva, Irena
Abstract : This study represents the first investigation into incidents of safeguarding concern in sport within the UK. Questionnaires were completed by 41 lead welfare officers from national governing bodies. A total of 652 cases were reported by a range of key stakeholders, covering a variety of different forms of abuse. Physical and sexual abuse were found to be the most frequently alleged forms of abuse. The majority of alleged perpetrators and victims were males. The need for a standardised form for collecting case data as part of normal practice is highlighted along with the necessity for training and support to manage safeguarding cases both internally and externally to sport organisations. Copyright © 2014 John Wiley & Sons, Ltd. 'Physical and sexual abuse were found to be the most frequently alleged forms of abuse' Key Practitioner Messages: A total of 652 safeguarding cases were managed in sport by this sample during 2011. Physical and sexual abuse were the most frequently reported. The majority of victims were boys. There is a need to collect standardised data regarding all cases.